1D and 2D modelling of a chemical process using the FM-II model: Rotary drum filter. (February 2018) - Ben Mohamed, Sameh; Boussaid, Boumedyen; Abdelkrim, Mohamed Naceur; Tahri, Charfeddine
This work treats the physical one-dimensional (1D) and two-dimensional (2D) modelling of a chemical process of filtration of slurry, which is the second step of phosphoric acid manufacture. This work focuses on the different physical laws involved in the filtration stage in order to obtain a simulator of the filter. In this work, we are interested in the 1D modelling of a rotary filter using all parameters and physical phenomena established in the filtration phase. Then, a 2D model emerged from the previous model by choosing both a temporal and a spatial variable. These two parameters are quite necessary for the construction of a 2D model based on the method of Fornasini–Marchesini (FM-II) to describe the dynamics of the system.